A micro cogeneration system with LNG cold utilization-part 2 : exergy analyses - Kanbur, Baris Burak (2018)
Exergy analyses provide to investigate the available work performance of thermal cycles. In this study, exergy analyses have been conducted for the conventional micro-cogeneration system and the Liquefied Natural Gas (LNG) cold utilized micro cogeneration system, respectively to detect exergy destruction and loss ratios which are related to second law analyses. In the LNG cold utilized micro-cogeneration system, the exhausted gas of micro turbine is supplied to the LNG vaporizer to change the phase of LNG from liquid to gas. Due to fact that exergy destruction and loss rates, exergetic efficiency decreases with the ambient air temperature increment by nearly 28%. Owing to the application of exhausted gas in the LNG vaporizer in the LNG cold utilized micro-cogeneration system, the exergy loss ratio decreases by approximately 81% when it is compared to the conventional micro-cogeneration system. At the same time, the exhausted gas temperature decreases nearly 2.93 K. Exergy destruction ratio is another evaluation criterion for exergy analyses and it is seen that the combustion chamber had a significant impact on the overall exergetic performance of both systems. The minimum exergy destruction rate belongs to the LNG pump and also the LNG vaporizer does not have a significant exergy destruction ratio.